1977
DOI: 10.1126/science.831273
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Transport Across Isolated Opercular Epithelium of Killifish: A Membrane Rich in Chloride Cells

Abstract: The opercular epithelium of Fundulus heteroclitus contains typical gill chloride-secreting cells at the high density of 4 X 10(5) cells per square centimeter. When isolated, mounted as a membrane, and short-circuited, it actively transports chloride ions from the blood side to the seawater side of the preparation. This preparation offers a useful approach to the study of osmoregulation in bony fishes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…This is also the case for the leakiness of tight junctions, which promote paracellular Na + extrusion across gill epithelium (Karnaky et al, 1977;Degnan and Zadunaisky, 1980). The decreased osmotic permeability of gill and opercular epithelia in fish exposed to strongly hyperhaline environments represents a qualitative shift in the adaptive strategy relative to the increase in osmotic permeability that occurs when euryhaline fish are acclimated from freshwater to regular seawater (35 g kg…”
Section: Osmoregulatory Strategies At Extreme Salinitiesmentioning
confidence: 99%
“…This is also the case for the leakiness of tight junctions, which promote paracellular Na + extrusion across gill epithelium (Karnaky et al, 1977;Degnan and Zadunaisky, 1980). The decreased osmotic permeability of gill and opercular epithelia in fish exposed to strongly hyperhaline environments represents a qualitative shift in the adaptive strategy relative to the increase in osmotic permeability that occurs when euryhaline fish are acclimated from freshwater to regular seawater (35 g kg…”
Section: Osmoregulatory Strategies At Extreme Salinitiesmentioning
confidence: 99%
“…The opercular epithelium lining the inside of the gill chamber of the teleost F. 1heteroclitu8 contains an abundance of chloride cells (Burns &( Copeland, 1950;Karnaky & Kinter, 1977) identical in fine structure to the chloride cells of the gill epithelium (Karnaky & Kinter, 1977). In a preliminary report, Karnaky, Degnan & Zadunaisky (1977) mounted the opercular epithelium of 100 % seawateradapted F. heteroclitw9 as a flat sheet between two halves of a Lucite chamber and demonstrated that the measured short-circuit current was equivalent to the net active secretion of CO-ions from the blood side to the seawater side of this epithelium. This third alternative approach to the study of teleost osmoregulation, the isolated, short-circuited opercular epithelium of F. heteroclitu8, avoids many of the technical problems involved in intact fish and isolated, perfused gill preparations and can provide some of the needed biophysical data required for a better understanding of teleost osmoregulation.…”
mentioning
confidence: 97%
“…Thus active Cl − extrusion would be reduced. To our knowledge, there is no published information on the effect of severe hypoxia on active ion transport rates in killifish in vivo, but in the isolated opercular epithelium of SW-acclimated killifish studied in vitro, complete anoxia reduces the active Cl − current by 75-83% (Karnaky et al, 1977;Barnes et al, 2014). This effect, together with the fact that the reduced TEP in the current study results in about a 70% increase in the electrochemical gradient driving Na + entry, suggests that the electrical response to hypoxia would be deleterious to ionoregulatory homeostasis in SW-acclimated killifish.…”
Section: Resultsmentioning
confidence: 99%